Sticking around: Plant persistence strategies on edaphic islands - Ottaviani, Gianluigi; Méndez-Castro, Francisco E.; Conti, Luisa; Zelený, David; Chytrý, Milan; Doležal, Jiři; Jandová, Veronika; Altman, Jan; Klimešová, Jitka (Diversity & distributions, 2022)
Aim Species on islands are at high risk of extinction due to environmental changes, including global warming, land‐use alterations and invasions. At local scales, extinctions can be offset by strategies promoting in situ persistence. We explored how persistence‐related traits of plants—that is, linked to belowground resource conservation, growth, size and longevity—on edaphic islands respond to variation in insularity and the environment (soil and microclimate), including intraspecific variability, which is rarely considered in functional island biogeography. We hypothesised that plants facing strong insularity and harsh soil conditions are characterised by enhanced persistence abilities. Location Shallow‐soil temperate dry grasslands on granite outcrops, Central Europe. Methods We focussed on edaphic island specialist species belonging to different life histories, namely clonal and non‐clonal perennial plants. We used linear and linear mixed‐effect models to examine intra‐ and interspecific trait patterns versus variation in insularity, soil and microclimate. Results Insularity tended to promote smaller plants (non‐clonal species) and belowground resource‐conservative strategies (both clonal and non‐clonal species), increasing the likelihood of local persistence. Soil also contributed largely to explaining persistence‐related trait patterns: plants growing in harsh soil conditions tended to be resource conservative. Clonal species are distinguished by highly consistent responses to variation in insularity and soil conditions, whereas non‐clonal plants showed distinct species‐specific responses. Main conclusions Our findings have important implications for the conservation biogeography of edaphic island plant specialists. Clonal species may be susceptible to local extinction should insularity or soil conditions vary, for example, due to abrupt changes in the geographical setting (e.g. habitat loss) or local environmental factors (e.g. N‐deposition). Non‐clonal species may instead face environmental changes differently; some will go extinct, whereas others will survive, depending on the prevailing abiotic pressures. This seems to challenge previous views that predicted clonal species to be the winners and non‐clonal species the losers against local extinction.